Peixes frugívoros e as implicações na diversidade de plantas em uma planície inundável neotropical - Araujo, Joisiane Karoline Mendes (2019)
Seed dispersal contributes to community structuring and maintenance of plant species diversity. Interactions between frugivorous fishes and plants are unique to wetlands (e.g., floodplains). Considering the importance of wetlands, understanding how the interaction between frugivorous fishes and plants contributes for the maintenance of diversity, allows us to explore evolutionary, ecological and economic approaches. Thus, in three chapters, we evaluated the ecological implications of mutualistic interactions between frugivorous fishes and plants on the floodplain of the Pantanal. In the first chapter, we evaluated whether fishes are selective or opportunistic in their use of fruits in floodplains. We found that the identity of preferred fruits, rather than their availability, had a stronger effect on the patterns of fruit consumed by fishes in this system. Such selectivity could increase the vulnerability of plant and fish populations to disturbance and influence ecological and evolutionary processes associated with frugivory by fish. In the second chapter, we evaluated the robustness of plant-frugivore networks to different extinction scenarios, using fish body size as a functional trait influencing seed dispersal and seed predation. Overall, the robustness to extinction of frugivorous fish decreased with selective loss of interactions involving large individuals. We predict that selective loss of big fish is likely to enhance the dominance of plant species with small seeds and decrease overall plant diversity. Our results show that networks of frugivorous fishes are complementary, and a scenario of decreasing abundance of big fish, driven by overfishing, will compromise the ecological and evolutionary processes involved in these unique plant-fish interactions. In the third chapter, we explored seed dispersal of herbaceous plants by fishes and discuss its potential importance for flooded savanna vegetation in the Pantanal. We found small fish with greater potential than large fish to consume and consequently disperse herbaceous seeds. Given evidence of functional complementarity in seed dispersal between large and small fish, here we contribute to understand the ecological and economic role of small fish in floodplains.